Incorporating Child Rights into Scheduling Decisions at the UN Commission on Narcotic Drugs - Damon Barrett; Diederik Lohman (Revue Internationale de Politique de Développement)
This paper focuses on the child rights implications of bringing new substances into the global drug control regime. Focusing on the examples of ketamine and khat, which in turn highlight the issues of access to medicines (SDG 3) and child labour (SDG 8), it outlines the process for placing substances under international control and the child rights implications of such decisions. To date, however, child rights law has not been featured in this procedure. While child rights law may not be determinative in terms of outcome, the chapter focuses on an important process in global drug policy governance. If decisions to place substances under international control within the drug control architecture of the United Nations engage the obligations of child rights treaties, then there is a strong case for formally taking the obligations arising under those treaties into account.